Integrated planning of natural gas and electric power systems - Odetayo, Babatunde; MacCormack, John; Rosehart, W.D.; Zareipour, Hamidreza; Seifi, Ali Reza (International journal of electrical power & energy systems, 2018)
•Integrated long-term planning of natural gas and electric power systems.•Probabilistic models for long-term planning of natural gas and power systems.•Cross-compensation of reliabilities in the integrated planning of energy systems.•Long-term energy systems planning under interdependent uncertain demands. Global electricity generation from natural gas is expected to continue in an upward trend in the coming years thereby increasing the interdependency between the electricity and the Natural gas transportation system. The reliability concerns associated with this interdependency has necessitated an integrated approach to planning both systems to achieve an overall system reliability. This paper proposes a planning approach that minimizes the capital and operational cost of the electricity and natural gas transmission system subject to probabilistic constraints such that a desired confidence level of supply is attained. A Chance constrained and reliability programming optimization model was proposed for solving the long-term integrated planning problem and their performance was compared by illustrating them on the standard IEEE 30 bus test system superimposed on the Belgian high-calorific gas network.